Spatial Analysis of Flood Prone Areas in Fena Leisela Subdistrict, Buru Regency - Philia Christi Latue (Journal of Innovation Information Technology and Application (JINITA), 2023)
Fena Leisela sub-district is often hit by floods in the rainy season. Floods that often occur in the Siwalalat sub-district are caused by the overflowing of the Waegeren river. The research used DEMNAS data and analysis using the Topographic Wetness Index method. The results of the inundation potential analysis are divided into three classes, namely low potential class with an area of 92,196.09 or 63.04%, medium class of 45,769.48 ha or 31.29%, and a high potential class of 936.12 ha or 5.67%. Waelana-Lana village (3,291.78 ha), Wamana Baru (1,349.33 ha), and Waspait (936.12 ha) are villages that have the largest area in the high flood hazard class in Fena Leisela Sub-district. In the medium flood class, Raheriat village (8,243.39 ha) is the village that has the largest area presentation compared to other villages and for the low flood hazard class, Wamlana village (14,811.98 ha), Waemite village (12,305.48 ha) and Waelana-lana village (1,680.33 ha) are the villages that have the largest area compared to other villages in Fena Leisela Sub-district. The results of this study are expected to be a reference for the government and the community in handling future floods to minimize the impact that occurs.